Job Expectations and Satisfaction Among Scientists - Feldy Marzena; Bojko Marta (Marketing of Scientific and Research Organizations, 2020)
The decreasing supply of qualified people ready to take up employment, observed for several years on the labour market, results in the strengthening of the employee’s position. The consequences of this process affect not only the companies but also scientific institutions. The employee’s market, which is shaped as a result of the following changes, forces employers to focus increasingly on activities aimed at attracting and retaining individuals who constitute their human capital. The aim of our article is to diagnose satisfaction levels of various job facets and differences in attachment to the workplace in groups of scientists with varied job expectation profiles. On this basis, it will be possible to indicate the job facets that scientific institutions should take into consideration in order to provide researchers with a high level of job satisfaction. To broaden knowledge about the subject, we used data collected by the National Information Processing Institute in 2017 in a nationwide representative sample of 840 scientists who were at various stages of their academic career, represented all areas of science and worked in all types of scientific units in Poland. By performing factor analysis and a clustering procedure on variables describing researchers’ job expectations we were able to categorize the respondents into three groups: 1) demanding, 2) aspiring and 3) unengaged. The demanding employees have high expectations in all job facets that we examined, i.e.: economic and organizational matters, developmental and social opportunities as well as employment flexibility. The aspiring scientists above all appreciate developmental and social opportunities more than other groups. On the contrary, the unengaged employees value developmental and social opportunities the least while other job facets are moderately significant for them. The survey of satisfaction of particular groups of scientists with their current employer indicates the need to focus the scientific institutions employing them on different aspects of work. In the case of demanding employees, it is important to take care of their economic well-being. On the other hand, in order to increase satisfaction from work of scientists from the aspiring group, it will be important to provide them with a higher level of satisfaction from the development and social sphere. The greatest challenge may be the satisfaction of unengaged employees who declare a relatively low general level of satisfaction with the workplace, and at the same time do not have well-established expectations towards the institutions employing them.